Adhesion of high performance thermoplastic composites: Development of a bench and procedure for kinetics identification. (November 2020) - Avenet, Julien; Levy, Arthur; Bailleul, Jean-Luc; Le Corre, Steven; Delmas, Jerôme
Graphical abstract: Abstract: Thermoplastic welding, tape placement, 3D printing, overmoulding or even thermostamping involve adhesion of thermoplastic polymer at high temperature. Build-up of the mechanical resistance between two substrates is usually assumed to be driven by the diffusion of macromolecules at the interface, called healing phenomenon. Moreover, in continuous processes, such as some used in manufacturing of composites for aerospace structures, cycles are very short. Thus, there is a need for quantifying the adhesion of such materials especially when processed for short durations. With this aim, a temperature and pressure controlled welding bench was designed to enable the welding of double cantilever beam samples for short time (down to 1 s). Adhesion of a carbon-PEKK composite was characterized over a wide range of residence times ranging from 1 s to 1 h. Three bonding regimes were observed, corresponding to different stages of the adhesion build-up at the interface. Finally, the healing kinetics was identified.